Evidence of helminthic infestation and efficacy of anthelminthic treatment in children investigated for eosinophilia - Rodić, Predrag; Ćazić, Marija; Škorić, Dejan; Lazić, Jelena; Milošević, Goran; Janković, Srdja; Krstovski, Nada (Vojnosanitetski pregled, 2024)
Background/Aim. The cause of eosinophilia often remains unelucidated. The aim of the study was to analyze causes and treatment approaches in children with eosinophilia in pediatric tertiary care hospital. Methods. The medical records of children investigated for eosinophilia (based on the International Classification of Diseases code D72.1) were retrospectively reviewed in the University Children’s Hospital, Belgrade, Serbia, from December 2011 to December 2022. A total of 105 children (62 boys; male:female ratio was 1:4) aged one month to 16.5 years (median 7.7 years) were diagnosed with eosinophilia. After excluding 15 of them due to incorrectly assigned diagnosis based on relative eosinophil number only, the remaining 90 children were grouped according to the severity of eosinophilia (mild, moderate or severe). Results. Serological analysis confirmed toxocariasis in six (6.7%) patients, while two (2.2%) had a confirmed nematode infestation (Ascaris lumbricoides and Enterobius vermicularis, respectively). Thirty-two (35.6%) children with eosinophilia and three with no true eosinophilia were diagnosed with helminthiasis ex juvantibus. Eosinophilia was ultimately explained by allergic/atopic conditions [19 (21.1%)], drug reactions [four (4.4%)], bacterial infections [nine (8.9%)], hematological problems [five (5.5%)], autoimmune disorders [three (3.3%)], unrelated congenital disorders (one), or as an isolated finding [seven (7.8%)]. In addition, one of the children without an increased absolute eosinophil number was diagnosed with eosinophilic esophagitis. A total of 56 (53.3%) children received anthelminthic treatment: 9 (90.0%) with severe eosinophilia, 19 (51.4%) with moderate, 23 (53.5%) with mild, and 5 (33.3%) children with no true eosinophilia. Most (42) of the children were given mebendazole only, while the remaining 14 (eight with severe, three with moderate, and three with mild) were also initially treated with mebendazole but subsequently shifted to albendazole due to the persistence of eosinophilia. In all treated children, eosinophilia and other relevant findings (if any) subsided in a matter of a few days to a few weeks after initializing treatment. Conclusion. Our results support the recommendation that unexplained eosinophilia of all levels of severity requires a standardized diagnostic approach. The results also provide some support for a potential rational basis for ex juvantibus administration of anthelminthic drugs in a fraction of children with eosinophilia without an obvious etiological explanation.
Keywords: anthelmintics; child; diagnosis; diagnosis, differential; eosinophilia; tertiary care centers; treatment outcome.